Prolonged analgesia by adding midazolam and hyperbaric bupivacaine in subarachnoid block for lower uterine caesarian section (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Oct;19(4):569-75The abstract of this article is available on the PubMed website